2016
DOI: 10.1117/12.2231601
|View full text |Cite
|
Sign up to set email alerts
|

The e-ASTROGAM gamma-ray space mission

Abstract: e-ASTROGAM is a gamma-ray space mission to be proposed as the M5 Medium-size mission of the European Space Agency. It is dedicated to the observation of the Universe with unprecedented sensitivity in the energy range 0.2 -100 MeV, extending up to GeV energies, together with a groundbreaking polarization capability. It is designed to substantially improve the COMPTEL and Fermi sensitivities in the MeV-GeV energy range and to open new windows of opportunity for astrophysical and fundamental physics space researc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…HARPO [13] with a gaseous detector, e-ASTROGAM [7] with a silicon tracker and even the Fermi-LAT [33]), and few generators take the photon polarisation into account. Besides our exact 5D generator, only G4:livermorepola tries to describe the angular asymmetry in the case of polarised photons.…”
Section: Polarisation Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…HARPO [13] with a gaseous detector, e-ASTROGAM [7] with a silicon tracker and even the Fermi-LAT [33]), and few generators take the photon polarisation into account. Besides our exact 5D generator, only G4:livermorepola tries to describe the angular asymmetry in the case of polarised photons.…”
Section: Polarisation Asymmetrymentioning
confidence: 99%
“…Several technologies are being considered to improve the angular resolution such as silicon wafer stacks (i.e., without tungsten converters) [1,2,3,4,5,6,7], liquid noble-gas time projection chambers TPC (argon [8], or xenon [9]) and emulsions [10].…”
Section: Introductionmentioning
confidence: 99%
“…The achieved spatial resolution is of order 2-3 degrees only, while spectral resolution, however, is sufficient for astrophysical detail studies from line shapes and centroid shifts for several lines and sources of interest [22]. Examples for proposed next-generation instruments [23,24] have demonstrated that about one order of magnitude improvements or more would be feasible, affordability assessment by the scientific funding communities set aside.…”
Section: Measuring Cosmic Gamma-ray Linesmentioning
confidence: 99%
“…Diffuse nuclear-line and annihilation-line emission will be discussed thereafter, with respect to the underlying source populations. 44 Ti ccSN interior nucleosynthesis 0.078 radioactive decay: 44 Ti ccSN interior nucleosynthesis 0.122 radioactive decay: 57 Ni supernova nucleosynthesis 0.158 radioactive decay: 56 Ni supernova nucleosynthesis 0.478 radioactive decay: 7 Be nova nucleosynthesis 0.511 positron annihilation nucleosynthesis, compact stars, binaries 0.812 radioactive decay: 56 Ni supernova nucleosynthesis 0.847 radioactive decay: 56 Co supernova nucleosynthesis 1.157 radioactive decay: 44 Ti ccSN interior nucleosynthesis 1.173 radioactive decay: 60 Fe,Co ccSN ejected nucleosynthesis 1.238 radioactive decay: 56 Co supernova nucleosynthesis 1.275 radioactive decay: 22 Na nova nucleosynthesis 1.332 radioactive decay: 60 Fe,Co ccSN ejected nucleosynthesis 1.634 nuclear excitation: 20 Ne cosmic ray / ISM interactions 1.809 radioactive decay: 26 Al massive-star and ccSN nucleosynthesis 2.230 neutron capture by H energetic nucleon interactions 2.313 nuclear excitation: 14 N cosmic ray / ISM interactions 2.754 nuclear excitation: 24 Mg cosmic ray / ISM interactions 4.438 nuclear excitation: 12 C cosmic ray / ISM interactions 6.129 nuclear excitation: 16 O cosmic ray / ISM interactions…”
Section: -4mentioning
confidence: 99%
“…For thick wafers (≈ 500 µm [47,48,49,50,51,52]), the effective polarization asymmetry, and therefore the dilution factor, are still low because multiple scattering remains an issue. It's only if very thin wafers can be made, held and launched (≈ 150 µm [53]) that there is some hope of a sizeable sensitivity to polarization (see Figs.…”
Section: γ-Ray Polarimetry With Pairs: Techniquesmentioning
confidence: 99%